2016
DOI: 10.1073/pnas.1604100113
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a stalled complex on the β-barrel assembly machine

Abstract: The assembly of β-barrel proteins into membranes is mediated by an evolutionarily conserved machine. This process is poorly understood because no stable partially folded barrel substrates have been characterized. Here, we slowed the folding of the Escherichia coli β-barrel protein, LptD, with its lipoprotein plug, LptE. We identified a late-stage intermediate in which LptD is folded around LptE, and both components interact with the two essential β-barrel assembly machine (Bam) components, BamA and BamD. We pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
112
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 85 publications
(120 citation statements)
references
References 48 publications
8
112
0
Order By: Relevance
“…The Bam machine has two essential OMP substrates: the LPS insertase LptD and BamA. LptD is the cell's most complicated OMP substrate: its folding requires both assistance from an additional essential OM lipoprotein (LptE) and disulfide bond rearrangement to achieve the oxidized, functional form (LptD OX ) (41,42). We found that cpxA24 Δlpp ΔrcsB cells lacking lolB produced the same levels of both BamA and LptD OX as lolB + controls (Fig.…”
Section: The Cpx Response Monitors Lipoprotein Trafficking and Protectsmentioning
confidence: 69%
“…The Bam machine has two essential OMP substrates: the LPS insertase LptD and BamA. LptD is the cell's most complicated OMP substrate: its folding requires both assistance from an additional essential OM lipoprotein (LptE) and disulfide bond rearrangement to achieve the oxidized, functional form (LptD OX ) (41,42). We found that cpxA24 Δlpp ΔrcsB cells lacking lolB produced the same levels of both BamA and LptD OX as lolB + controls (Fig.…”
Section: The Cpx Response Monitors Lipoprotein Trafficking and Protectsmentioning
confidence: 69%
“…Ability to recognize the substrates is an essential function of BamD, and the peptides containing the β signal, which bind BamD, are toxic because they inhibit β barrel assembly (34). However, the function of BamD is not limited to the initial substrate recognition, because BamD remains closely associated with the substrate throughout entire OMP assembly and must play an active role during this process (40; 56). One of these roles is to regulate BamA conformational cycling through the direct interaction with P5 (see BamA conformational mobility section for more details) (75; 76).…”
Section: Overall Architecture Of the Bam Complexmentioning
confidence: 99%
“…The rearrangement of [1,2] oxidized LptD into the mature form with non-consecutive disulfide bonds ([1,3][2,4]-LptD) happens after [1,2] LptD is folded around LptE, which brings C-terminal Cys residues in proximity to N-terminal Cys residues (11). Accordingly, conditions that limit LptE stall LptD folding and LptD accumulates in the [1,2] form (56). In addition, when LptE is limiting the [1,2] form of LptD does not accumulate on the Bam complex, demonstrating that LptE is recognized by the Bam complex first, and suggesting that LptE is required not only for LptD folding but also for a recognition of LptD by the Bam complex (56).…”
Section: Experimental Evidence For β-Barrel Folding At the Periplamentioning
confidence: 99%
See 2 more Smart Citations